A prospective study comparing the efficacy and safety of two sublingual birch allergen preparations. Issue 1 (23rd July 2014) - Klimek, Ludger; Sperl, Annette; van Twuijver, Esther; van Ree, Ronald; Kleinjans, Huub; Boot, Johan Diderik; Pfaar, Oliver
Abstract: Background: SUBLIVAC FIX Birch (SUB‐B) is a liquid oral preparation of Betula verrucosa pollen extract for the treatment of allergic rhinitis/rhinoconjuctivitis induced by birch pollen. The major allergen content of SUB‐B and Staloral Birch (Stal‐B) have been shown to be comparable. In order to compare the clinical efficacy and safety of both products, the present study was designed to investigate efficacy of treatment with SUB‐B compared to Stal‐B by means of reduction in allergy symptoms assessed by a titrated nasal provocation test (TNPT) in subjects suffering from IgE mediated allergy complaints triggered by birch pollen. Methods: A prospective, randomized, open, blinded endpoint (PROBE), controlled, single‐centre study in 74 birch allergic adults was performed. Treatment consisted of either SUB‐B (10, 000 AUN/ml) or Stal‐B (initial phase 10 I.R./ml and maintenance phase 300 I.R./ml) for 16–20 weeks at maintenance dose. The primary efficacy outcome was defined by the difference in change of the TNPT‐threshold dose between the two treatment groups at baseline and after completion of treatment. Secondary outcomes included determination of birch pollen specific IgE and IgG levels, safety lab and ECG. During the first 30 days of treatment, subjects were requested to fill out a diary concerning compliance with study medication, occurrence of AEs and the use of concomitant medication. Results: Analysis of the primary efficacy parameter showed that the percentage of subjects showing a beneficial treatment effect was similar in both treatment groups, 33.3% for SUB‐B vs. 31.4% for Stal‐B in the intention to treat population. Evaluation of the immunologic response, showed that treatment with SUB‐B and Stal‐B induced similar increases (approximately 2 times) in IgE, IgG and IgG4 specific for Bet v 1. In total, 143 related adverse events (AEs) were reported. The majority of the AEs was of mild intensity. The same pattern of AEs was observed for both products. No clinically relevant changes in other safety parameters, such as safety laboratory parameters, vital signs, physical examination and ECGs were observed. Conclusion: Taken together, treatment with both products was effective by means of reduction in allergic symptoms during a TNPT. In addition, safety analysis revealed a good tolerability of both SLIT extracts.